Positioning Strategy for Excelso Coffee Buyers At Mayfair Bandung - Supriyoso, Patria; Supriadi, Dede (Economic: Journal Economic and Business, 2022)
The activity of drinking coffee is only intended to relieve drowsiness, but has also become part of a modern lifestyle, changes in culture, environment and technology make coffee not only considered as an ordinary drink, but has become an icon of self-identity and a symbol of socialization. . In addition, the majority of Indonesian people are coffee fans. Excelso comes with a coffee cafe where executives and professionals hang out with segmentation, targeting and positioning, bringing hangout places and places designed to be as comfortable as possible so that they feel at home in Excleso cafe, with drinks and food that are all coffee. In addition, Excelso's innovation is the presence of coffee from all over Indonesia with various flavors and coffee grounds with packaging that can be brewed at home as well as services and a comfortable place for Excelso buyers so that they can promote to their colleagues and friends to come to the Excelso cafe.